Soil Seed Banks of Continental Grasslands with Different Water Regimes—A Comparative Study from the Aspect of Recovery Potential - Judit Schellenberger; Péter Csontos; Ádám Csorba; Attila Lengyel; Gábor Málnási Csizmadia; Orsolya Szirmai; Károly Penksza; Szilárd Czóbel (Agronomy, 2022)
Due to the threats posed by climate change and landscape alteration, there is an increasing need to better understand using seed banks of continental grasslands as a possible aid to conservation and restoration. Here, the soil seed bank of a wet grassland type, an ecotone and a semi-dry grassland type, all formed along a slope in NE Hungary, were compared from the aspect of recovery potential. For this, a vegetation survey and a seedling emergence examination were performed. The seed banks of the three grassland types differed significantly in terms of density. It was significantly higher in both the wet and the ecotone grassland types than in the semi-dry one. The seed banks of the three grassland types proved to be very similar in terms of diversity. The floristic similarity between the vegetation and the seed banks was much higher in both the wet and the ecotone grassland types than in the semi-dry one. Most of the abundant species of the vegetation had transient seed banks, but more of the characteristic species of the wet and the ecotone grassland types maintained dense and/or persistent seed banks than those of the semi-dry one. In the case of degradation, a complete recovery is not ensured by the seed bank of either studied grassland type; however, compared to that of the semi-dry grassland, the wet grassland’s seed bank better supports an increase in diversity within a limited period. In the case of restoration, within five years after destruction, it could be more rewarding to deal with wet grassland types prior to dry ones.